Flourodeoxyglucose positron emission tomography scan may be helpful in the case of ductal variant prostate cancer when prostate specific membrane antigen ligand positron emission tomography scan is negative. Issue 4 (28th March 2017) - McEwan, Louise M; Wong, David; Yaxley, John
Summary: Gallium‐68 prostate specific membrane antigen ligand (Ga‐68 PSMA) positron emission tomography/computed tomography (PET/CT) scanning is emerging as a useful imaging modality for the staging of suspected and known recurrent or metastatic prostate cancer and in staging of newly diagnosed higher grade prostate cancer. However, we have observed at our institution that in some cases of the more aggressive ductal variant, Ga‐68 PSMA uptake has sometimes been poor compared with prominent 18‐flourodeoxyglucose (F‐18 FDG) avidity seen in F‐18 FDG PET/CT, which would suggest that FDG PET/CT scans are important in staging of ductal pattern prostate cancer.